Anti-cytokine agents for anhedonia: targeting inflammation and the immune system to treat dimensional disturbances in depression. Issue 12 (December 2018) - Lee, Yena; Subramaniapillai, Mehala; Brietzke, Elisa; Mansur, Rodrigo B.; Ho, Roger C.; Yim, Samantha J.; McIntyre, Roger S.
The etiology of mood disorders is mechanistically heterogeneous, underscoring the need for a dimensional approach to identify and develop targeted treatments in psychiatry. Accumulating evidence implicates inflammation as an important contributor to the pathophysiology of depression and presents the immune system as a viable therapeutic target that may be more proximate to the pathogenic nexus of brain-based disorders in specific subpopulations. Anhedonia is a transdiagnostic (e.g. Parkinson's disease, diabetes mellitus, rheumatic diseases), yet specific, and clinically relevant symptom dimension subserved by well-characterized neurobiological and neurophysiological substrates of the positive valence systems (PVS). Brain circuits, nodes, and networks, as well as cellular and molecular pathways (e.g. dopaminergic transmission; excitotoxicity; synaptic plasticity), subserving anhedonia are preferentially affected by inflammatory processes. To our knowledge, no published randomized, controlled clinical trial in populations with mood disorders has, to date, primarily sought to determine the effects of an anti-inflammatory agent on PVS functions or pathophysiology. Three ongoing clinical trials aim to investigate the effects of anti-TNF-alpha biologic infliximab on measures of anhedonia [ClinicalTrials.gov identifier: NCT02363738], motivational behavior and circuitry [ClinicalTrials.gov identifier: NCT03006393], and glutamatergic changes in the basal ganglia [ClinicalTrials.gov identifier: NCT03004443] in clinical populations with unipolar or bipolar depression. Positive results would further instantiate the relevance of inflammatory processes and the immune system in the pathophysiology of mood disorders and provide the impetus to develop scalable treatments targeting inflammation and the immune system to mitigate transdiagnostic, dimensional disturbances in brain-based disorders.